Bulgarian Joyce teaching and wake boundary breaking during the quarantine (Philology, 2024)
In this article, I provide a study of my experiences as a lecturer teaching the works of the Irish author James Joyce to university students in Bulgaria, at BA and MA levels. As a complete body of research, it provides insight into the specifics of how Bulgarian students idiosyncratically view and appreciate Joyce. I provide as my initial case study Bulgarian students who have completed a semester-long elective course on his 1922 novel Ulysses. It outlines the difficulties that they have encountered within the course; for instance, how Irish culture and its history provide an obstacle since few parallels exist between it and the Slavic world. I have incorporated students’ responses to an in-depth questionnaire which inquired about what challenges they faced as readers and how they surmounted them. Throughout the text, I detail the pedagogical methods I have employed to engineer it towards their specific educational demographic, largely focusing on how to make the book as “unintimidating” as possible. The second section is a case study of work carried out by a group of 5 students who comprise a Finnegans Wake reading group in Bulgaria, specifically during the time period of the COVID-19 pandemic “lockdown”. It is my conclusion that they embraced radical interpretive methods of tackling Joyce’s final work, Finnegans Wake (1939), involving highly experimental concepts, to feel a sense of freedom during the difficult psychological stresses brought upon by the pandemic.
Keywords: Joyce; Ulysses; COVID-19; Finnegans Wake; експериментални прочити